P118 THE RISK OF DIARRHEA AND COLITIS IN PATIENTS WITH ADVANCED MELANOMA UNDERGOING IMMUNE-CHECKPOINT INHIBITOR THERAPY. (18th January 2018) - Tandon, Parul; Bourassa-Blanchette, Samuel; Bishay, Kirles; Parlow, Simon; Laurie, Scott A; McCurdy, Jeffrey D
Abstract: Background and Aim: Anti-cytotoxic-T-lymphocyte associated antigen-4 (anti-CTLA4), and anti-programmed cell death 1 (anti-PD1) immunotherapies are considered first-line treatments for advanced melanoma. However, the use of these agents is limited by gastrointestinal toxicity such as diarrhea and colitis. The risk of developing these adverse events is poorly defined. As such, our aim was to determine the incidence and relative risk of diarrhea and colitis due to each class of immunotherapy in patients with advanced melanoma. Methods: A systematic search of electronic databases was performed through October 2016 for clinical trials assessing anti-PD1 (nivolumab or pembrolizumab) or anti-CTLA4 (ipilimumab or tremlimumab) immunotherapy in advanced melanoma. Studies that reported diarrhea and colitis using standardized clinical definitions according to the common terminology criteria for adverse events were included. The pooled incidence and the weighted relative risk estimates with 95% confidence intervals (CI) were calculated using random-effects model. Results: Eighteen studies were included: 6 studies (1537 patients) with PD-1 inhibitors and 15 studies (3116 patients) with CTLA-4 inhibitors. The incidence of all-grade diarrhea was 13.7% (95% CI, 10.1–17.2%) for anti-PD-1 and 35.4% (95% CI, 30.4–40.5%) for anti-CTLA-4. The incidence of all-grade colitis was 1.6% (95% CI, 0.7–2.4%) for anti-PD-1, and 8.8% (95% CI, 6.1–11.5%) for anti-CTLA-4. When PD-1 inhibitors were compared directly with CTLA-4 inhibitors, the relative risk of all-grade diarrhea was 0.58 (95% CI, 0.43–0.77), and the relative risk of all-grade colitis was 0.16 (95% CI, 0.05–0.51). Conclusion: Diarrhea and colitis are common toxicities associated with immunotherapy for advanced melanoma and appear to be more common with anti-CTLA4 antagonists.